Pemikiran Ibnu Khaldun Tentang Kebijakan Fiskal Khusus Pajak dan Relevansinya Dalam Menghadapi Resesi di Indonesia - Sukmalia, Dwita; Saputri, Ida Yuliana; Hak, Nurul; Oktarina, Amimah (Jurnal BAABU AL-ILMI: Ekonomi dan Perbankan Syariah, 2021)
Ibn Khaldun is an Islamic scholar with various works, especially in the muqaddimah book which explains the principles of taxation. According to Ibn Khaldun, the imposition of low taxes on the people will make the people more incentivized to do business and develop the business world. On the other hand, the imposition of high taxes on the people will be reluctant to pay taxes so that the production done by the people will decrease and affect the tax revenue itself. The purpose of this study was to determine the relationship between Ibn Khaldun's theory and the current downturn in economic growth. This research method is library research research with a descriptive qualitative approach with the data source used is secondary data consisting of the book "muqaddimah" and other theories derived from books, journals, and official websites that are relevant to the research. The data that has been collected is analyzed using the Content Analysis Method. This study concludes that Ibn Khaldun's thoughts are very relevant when applied in facing the recession in Indonesia